2016
DOI: 10.1093/jrr/rrw018
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of implant quality between intraoperatively built custom-linked seeds and loose seeds in permanent prostate brachytherapy using sector analysis

Abstract: We compared the implant quality of intraoperatively built custom-linked (IBCL) seeds with loose seeds in permanent prostate brachytherapy. Between June 2012 and January 2015, 64 consecutive prostate cancer patients underwent brachytherapy with IBCL seeds (n = 32) or loose seeds (n = 32). All the patients were treated with 144 Gy of brachytherapy alone. Brachytherapy was performed using a dynamic dose calculation technique. Computed tomography/magnetic resonance imaging fusion-based dosimetry was performed 1 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 26 publications
1
15
1
Order By: Relevance
“…To date, many studies compared stranded seeds to loose seeds [ 9 , 13 , 14 , 19 , 20 , 21 ], but few studies have compared the implant quality of linked seeds with that of loose seeds for prostate brachytherapy [ 17 , 22 , 23 , 24 , 25 ]; however, until now, there have been no reports about the plan reproducibility of linked seeds. Generally, intraoperative dosimetry based on ultrasound would not predict biochemical outcome [ 26 ].…”
Section: Purposementioning
confidence: 99%
“…To date, many studies compared stranded seeds to loose seeds [ 9 , 13 , 14 , 19 , 20 , 21 ], but few studies have compared the implant quality of linked seeds with that of loose seeds for prostate brachytherapy [ 17 , 22 , 23 , 24 , 25 ]; however, until now, there have been no reports about the plan reproducibility of linked seeds. Generally, intraoperative dosimetry based on ultrasound would not predict biochemical outcome [ 26 ].…”
Section: Purposementioning
confidence: 99%
“…This study demonstrated the dosimetric advantages of IBCL over LS for PPB. Several reports comparing DVH parameters between IBCL and LS found that prostate DVH did not differ between the two groups [ 22 , 23 , 24 , 25 ]. However, Jarusevicius et al .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the merits of IBCL over LS [ 21 , 22 , 23 , 24 , 25 ]. Jarusevicius et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations